KAJIAN HUKUM TENTANG PENGUKURAN DAN PEMETAAN UNTUK PENDAFTARAN TANAH DITINJAU DARI PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 1 TAHUN 2017 TENTANG PERUBAHAN ATAS PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL NOMOR 35 TAHUN 2016 TENTANG PERCEPATAN PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP - Garda Viska Putra; Hudali Mukti (Yuriska: Jurnal Ilmiah Hukum, 2018)
The measurement and mapping of land parcels for land registration is the initial subject in the framework of land certification to obtain a land title certificate. Problems and constraints that occur in the measurement and mapping of land parcels if not given a solution that can certainly cause more land disputes. Complete Systematic Land Registration is one of the efforts of the Ministry of Agrarian Affairs and Spatial Planning or the National Land Agency of the Republic of Indonesia in order to resolve the problems that occur, including the uncharted land parcels with old land titles and other fields that have not been granted land titles. a method of measuring the old parcels of land that are not in accordance with the current conditions, parsing land parcels that have experienced land disputes.